2012
DOI: 10.1186/1477-7827-10-62
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivodevelopment of mice morulae after storage in non-frozen conditions

Abstract: BackgroundInterchange of genetically modified (GM) mice between laboratories using embryos provides several advantages. Not only is transport stress avoided, but also the health status of the recipient colony is not compromised. Embryos do not need to be shipped in frozen stage, which requires expensive packaging in addition to a certain degree of expertise in order to freeze and thaw them correctly. The aim of this study was to examine different storage conditions and their effect on embryo viability in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…This is not surprising since in our previous work, we observed a certain development delay in porcine morulae preserved for up to 72 h at 25 °C or 37 °C, with the delay being most marked at 25 °C 4,6 . Our data suggest that the metabolism of pig embryos is severely reduced at temperatures below 20 °C, an effect that could be related to the misregulation of genes that play important roles in embryo development and cell proliferation and alterations in other molecular events, as previously reported for mice embryos stored at refrigeration temperatures 13,15 . Although the developmental arrest observed in the stored embryos was temporal, their final developmental stage was equally delayed including a lower total cell number compared to controls.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This is not surprising since in our previous work, we observed a certain development delay in porcine morulae preserved for up to 72 h at 25 °C or 37 °C, with the delay being most marked at 25 °C 4,6 . Our data suggest that the metabolism of pig embryos is severely reduced at temperatures below 20 °C, an effect that could be related to the misregulation of genes that play important roles in embryo development and cell proliferation and alterations in other molecular events, as previously reported for mice embryos stored at refrigeration temperatures 13,15 . Although the developmental arrest observed in the stored embryos was temporal, their final developmental stage was equally delayed including a lower total cell number compared to controls.…”
Section: Discussionsupporting
confidence: 77%
“…Although the developmental arrest observed in the stored embryos was temporal, their final developmental stage was equally delayed including a lower total cell number compared to controls. However, this situation may not be relevant for two main reasons; firstly, we previously reported that developmentally delayed stored pig embryos retained the capacity to develop in vivo 4,6 ; and secondly, although the relevance of a cell number limit is not yet fully understood, embryos with significantly lower cell numbers do not exhibit a compromised implantation capacity, at least in rodents 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cold-transport system of two-cell embryos is a useful technique to transport genetically engineered mice without the shipment of live animals. There are several studies that have improved the storage medium of two-cell mouse embryos [ 1 , 3 , 4 , 7 , 8 , 11 , 18 , 19 ]. Previously, we reported that NAC improved the developmental rate of two-cell embryos after cold storage and prolonged the storage period up to 96 h [ 6 ].…”
Section: Discussionmentioning
confidence: 99%